The seeds of change - Snelling, Lauraine; Giron, Kiersti (Snelling, Lauraine. Leah's garden, 2021)
"Larkspur Nielsen is ready for change, frustrated by the small-mindedness of her Ohio hometown and its lack of opportunity for her or her younger sisters. But the push to leave comes faster than she ever expected when several of her bold actions for justice earn her vindictive enemies. Overnight, they must pack up and ready to make a new life out West, hoping to escape notice and any opportunities for revenge. Knowing that four women traveling together will draw unwanted attention, Larkspur dons a disguise, passing herself off as 'Clark' Nielsen accompanying his three sisters. But maintaining the ruse is more difficult than Larkspur imagined, as is protecting her headstrong, starry-eyed sisters from difficult circumstances and available young men. Will reaching a safe place to call home ever be possible?"--